Using Creative Art Forms in Managing Autism at Little Haven School and Evergreen Autistic Academy in Ghana - Panin Kwame Baah, Owusu; Panin Edwina, Owusu; Ezekiel, Martey; Freeman Tetteh, Osabutey; Stephen, Alale (International Journal of Social Science, Education, Communication and Economics, 2024)
The study aims to show diverse ways of autism management in Ghana by exploring the potential benefits of using creative art forms as a therapeutic approach in special needs education with the help of assistive technology. Many individuals with autism face challenges in sensory processing. There is a growing need for effective intervention and support for people with autism in special education using creative art forms in Ghana. Creative arts such as painting, sculpture and poetry have shown promises in promoting communication, self-confidence, creativity, social interaction and emotional expression in people with autism. These art forms provide powerful tools for autistic people to interact with their friends and families around them in Ghana and the world with the help of assistive technology. The study explored the different approaches, methods and results of these interventions by using qualitative multiple case studies at Little Haven School and Evergreen Autistic Academy in Ghana. The study employed photographs, interviews and observations as research instruments. The results of this study contribute to the development of evidence-based practices which helps inform policy makers, educators, therapists and other stakeholders involved in autism support. Ultimately, the goal is to improve the well-being and quality of life of people with autism in Ghana and their families by promoting inclusive and accessible interventions that harness the power of creative art forms using assistive technology.